The lost legions : cultural contact in colonial Australia - Paterson, Alistair, 1968- (Lanham, MD : Altamira Press, 2008)
"The Lost Legions explores the cultural interactions between indigenous peoples and European settlers. Paterson draws especially on archaeological evidence from central Australia, where European pastoralists found themselves in the heart of the territory of the Aborigine Arabana people. Paterson also considers other sources of information - such as oral histories, onomastics, and evidence of culture contact in the Americas and southern Africa - to develop a broad understanding of what happens when such different civilizations encounter one another."--BOOK JACKET.
Prologue: Central Australia from a cessna -- The lost legions : historical pastoral industries, culture contact, and colonialism -- The ends of the earth were our portion -- Pangki Warruna/Strangways Springs Sheep Station (central Australia) -- A documentary history of Strangways Springs Station -- The texture of agency -- Further down the wallaby track -- Listing the legions -- Epilogue: Central Australia from a Cessna.
Includes bibliographical references and index.
Keywords: Aboriginal Australians, Treatment of -- History; Aboriginal Australians -- First contact with Europeans; Aboriginal Australians -- Cultural assimilation; Acculturation -- Australia; Economic sectors - Agriculture and horticulture - Pastoral industry; Technology - Glass; Occupations - Pastoral industry workers; Arabana / Arabunna people (L13) (SA SH53-03); Art - Rock art - Engraving; Sites - Excavations; Australia -- Race relations; Anna Creek (North West Central SA SH53-03); Inthanoona (WA East Pilbara SF50-07); Pangki Warruna / Strangways Springs (West SA SH53-08)